War memorial: The Calling Blighty films and remembrance. (September 2019) - Hawley, Steve
The Calling Blighty series of nearly 400 films were messages from servicemen in India and Burma to be shown to families in local cinemas at the end of the Second World War. They are remarkable because of their cinematic quality and the men's direct address to camera, and the 64 remaining films reveal much about family memories, public remembrance and representation of the Northern voice on screen. Along with Marion Hewitt of the North West Film Archive, the author has been engaged in an ongoing project to find the relatives of the men of the 'Forgotten Army' in the films and recreate the screenings. These ritual ceremonies of remembrance have been augmented by a media memorial, a Channel 4 TV documentary about the project and creative critical reflection through an experimental artist's film, drawing on the archive material. This analysis of the project looks at the relationship of the Blighty films to wartime film and documentary, in particular, as well as soldier self-representation, and their implications for both family and communal remembrance.